2014
DOI: 10.1123/jtpe.2013-0069
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Teachers’ Self-Efficacy and Students’ Motivation, Atmosphere, and Satisfaction in Physical Education

Abstract: The purpose of this study was to confirm the relationships among teachers’ self-efficacy, and students’ learning motivation, learning atmosphere, and learning satisfaction in senior high school physical education (PE). A sample of 462 PE teachers and 2681 students was drawn using stratified random sampling and cluster sampling from high schools in Taiwan. The research instruments were the Teachers’ Self-Efficacy Scale, and students’ Learning Motivation Scale, Learning Atmosphere Scale, and Learning Satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 37 publications
2
42
0
11
Order By: Relevance
“…One self-efficacy subscale of this instrument measures efficacy for teaching students with special needs in regular PE class. The importance of self-efficacy for PE teachers was emphasized by Pan's (2014) findings showing that there is a positive causal relationship among teachers' selfefficacy and students' learning motivation, learning atmosphere, and learning satisfaction in senior high school physical education. Hutzler, Zach, and Gafni (2005) applied the selfefficacy instrument to students of PE teacher education in regard to the inclusion of students with disabilities in general physical education.…”
Section: Self-efficacymentioning
confidence: 99%
“…One self-efficacy subscale of this instrument measures efficacy for teaching students with special needs in regular PE class. The importance of self-efficacy for PE teachers was emphasized by Pan's (2014) findings showing that there is a positive causal relationship among teachers' selfefficacy and students' learning motivation, learning atmosphere, and learning satisfaction in senior high school physical education. Hutzler, Zach, and Gafni (2005) applied the selfefficacy instrument to students of PE teacher education in regard to the inclusion of students with disabilities in general physical education.…”
Section: Self-efficacymentioning
confidence: 99%
“…At high education level, it has been reported that lecturers' competence has positive and significant effects on students' satisfaction (Sahin, 2014;Seng, 2013;Winahyuningsih & Edris, 2012;Rahmawati 2013;Lee, 2008;Wu et al, 2010). Of course, there are other factors that influence students' satisfaction in learning that go hand in hand with teachers' competence factors (Widoyoko and Rinawati, 2012;Asto, 2012;Machali, 2011;Wahjanto, 2007;Sutardi and Sugiharsono, 2016;Al-Ajami and Soeharto, 2014;Pan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Que el alumnado perciba que el docente muestra un mayor interés hacia las clases favorece y mejora el clima de aprendizaje que se genera en el aula, sintiéndo-se el alumno más cómodo y comunicativo tanto con el docente como con los compañeros. Este hecho se relaciona directamente con la autoeficacia del docente (Pan, 2014).…”
Section: Discussionunclassified